TWEAK Promotes the Proliferation of Squamous Cell Carcinoma Cells Through Activating cIAP1 Signals - Liang, Lili; Cheng, Chuantao; Hu, Guanglei; Wang, Xuening; Liu, Jing; Yan, Zhu; Zeng, Weihui; Xia, Yumin (Frontiers in Oncology, 2020)
Recent studies showed that tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) induces the proliferation of squamous cell carcinoma (SCC) cells. However, the precise mechanism underlying such effect of TWEAK remains unclear. This study was designed to elucidate the role of cellular inhibitor of apoptosis 1 (cIAP1) in TWEAK-induced proliferation of SCC cells. Human SCC cells (SCC-13, A431, and SCC-9) were cultured in vitro, receiving the stimulation of TWEAK or TNF-related apoptosis-inducing ligand (TRAIL). We found that TWEAK induced cytoplasmic cIAP1 importation and RIP1 ubiquitination in cells, followed by the activation of canonical nuclear factor kappa B signals. MV1, a cIAP1 inhibitor, abrogated TWEAK-induced proliferation of these cells. Moreover, the interaction between TWEAK and its receptor, fibroblast growth factor-inducible 14 (Fn14), enhanced the expression of TRAIL receptor types 3 and 4 (TRAIL-R3/4). Furthermore, the transfection of TRAIL-R3/4 siRNA abrogated the promotion effect of TWEAK on SCC-13 cell proliferation and cIAP1 expression. Therefore, TWEAK/Fn14 interaction promotes the proliferation of SCC cells through activating cIAP1 signals. Targeting the downstream cIAP1 signals might attenuate the effect of TWEAK on SCC cells.